Unexplained entry dyspareunia secondary to metallic needle - Yi-Jen Chen; Ben-Shian Huang; Wen-Hsun Chang; Shun-Fen Chen; Shu Yu; Peng-Hui Wang (Wolters Kluwer Medknow Publications, 2012)
Chronic and persistent dyspareunia is always challenging for the selection of adequate diagnostic management and therapeutic decision-making. A 72-year-old woman had a 53-year history of chronic and persistent entry dyspareunia. After appropriate diagnostic measures, including ultrasonography, plain film, and computed tomography, the patient underwent removal of a detected metallic needle from the perineum.